1988
DOI: 10.1007/bf00189271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three pollination methods on embryo development and seedset in intra- and interspecific crosses between seven Lilium species

Abstract: Interspecific crosses were made between seven Lilium species, viz. L. candidum, L. concolor, L. dauricum, L. henryi, L. longiflorum, L. nepalense and L. rubellurn. A complete diallel cross was carried out between these seven species, including selfand intraspecific pollinations using three pollination methods: normal pollination on the stigma, pollination on the ovary after cutting the style, and pollination on the stigma with the aid of' mentor' (non-functional, compatible) pollen. Embryo rescue, starting 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The conventional breeding of lily species has provided novel cultivars with a resistance to viral diseases, a tolerance for unfavorable culture conditions, and an ability to express special flower colors and forms (Van Tuyl et al 1988). For half a century, the limitations of obtaining cross-combinations in lilies because of the incompatibility and incongruity between different varieties have been known (Emsweller and Stuart 1948).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional breeding of lily species has provided novel cultivars with a resistance to viral diseases, a tolerance for unfavorable culture conditions, and an ability to express special flower colors and forms (Van Tuyl et al 1988). For half a century, the limitations of obtaining cross-combinations in lilies because of the incompatibility and incongruity between different varieties have been known (Emsweller and Stuart 1948).…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these difficulties, Watts (1967) obtained the seeds of some selfed plants and achieved many crosses of Lilium by using intrastylar pollination. Van Tuyl et al (1988, 1991 developed and established lily pollination methods for producing interspecific hybrids by utilizing the cut-style technique. However, these methods cannot be used to cover all of the combinations expected.…”
Section: Introductionmentioning
confidence: 99%
“…Post-fertilization barriers impeding interspecific hybridization in the Brassicaceae [5] and Liliaceae [6] have been overcome by using ovary culture. Ovary culture methods which support maturation of viable seeds have been developed for A. cepa [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto various techniques have been applied successfully to overcome pre-and post-fertilization of incompatibility. For example, it has been reported that prefertilization barriers can be bypassed by using methods such as the cut style technique, the grafted style method, plant growth regulator treatment, and in vitro pollination (Van Tuyl et al 1988, 1991Li and Niimi 1995;Niimi et al 1999); post-fertilization barriers can be overcome by embryo rescue techniques such as embryo culture (Okazaki et al 1994), ovule culture (Niimi et al 1996), ovules-withplacental-tissue culture (Obata et al 2000), and ovary slice culture (Kanoh et al 1988;Fernández et al 1996;Arzate-Fernández et al 1998;Chi 2002).…”
Section: Introductionmentioning
confidence: 99%